Penggunaan Model PBL Berbantuan Media Diorama Untuk Meningkatkan Berpikir Kritis Materi Ekosistem Sekolah Dasar - Adila, Adnin Cahyadi; Hadiwijaya Z, Rizki; Pratama, Febri Fajar (QUANTUM: Jurnal Pembelajaran IPA dan Aplikasinya, 2025)
This study aims to determine the improvement of students' critical thinking skills in the planning and implementation of the Problem-Based Learning (PBL) model assisted by diorama media on the ecosystem material in Grade V at SDN Cibungkul. The research method used is classroom action research (CAR), conducted in two cycles consisting of four stages: planning, implementation, observation, and reflection. The results of this study show that prior to the intervention, the percentage of students demonstrating critical thinking was 23%. In the first cycle, it increased to 59%, and in the second cycle, it reached 86%, which is an increase of 63% from the pre-intervention stage. Therefore, the result of this study is that the average level of students' critical thinking skills reached 83.4. Thus, the use of the Problem-Based Learning (PBL) model assisted by diorama media can improve students' critical thinking skills in learning about ecosystems.